Challenges in the management of haemophilia on transition from adolescence to adulthood. (17th December 2015) - Brand, Brigitte; Dunn, Spencer; Kulkarni, Roshni
Abstract: Patients with haemophilia undergo many transitions during their lives, but the period between adolescence and adulthood is particularly challenging. During this time, the patient must deal with all of the typical biological, social and emotional changes associated with this phase of life, whilst at the same time, adapting his lifestyle to the needs of his condition, transferring from paediatric to adult services and, most importantly, accepting increasing (and ultimately full) responsibility for managing his condition. Parents may also find their diminishing role equally challenging. Perhaps not surprisingly, given the challenges that adolescents face, treatment adherence during this time is generally low, which can lead to recurrent joint bleeds, chronic pain and reduced quality of life. To address the challenges, it is critical that a transition programme is put in place that meets the needs of not only the patient, but also his parents and healthcare providers. Key elements of the plan are a multidisciplinary approach, early planning, patient education and appropriate follow‐up. A successful programme will equip all parties with the skills to deal with the challenges of transition from adolescence to adulthood, ensuring that the benefits of treatment in childhood are maintained, thus optimising health outcomes and quality of life.